Tailoring pyridine bridged chalcogen-concave molecules for defects passivation enables efficient and stable perovskite solar cells - Muhammad Azam; Yao Ma; Boxue Zhang; Xiangfeng Shao; Zhongquan Wan; Huaibiao Zeng; Haomiao Yin; Junsheng Luo; Chunyang Jia (Nature Communications)
Abstract Suppressing deep-level defects at the perovskite bulk and surface is indispensable for reducing the non-radiative recombination losses and improving efficiency and stability of perovskite solar cells (PSCs). In this study, two Lewis bases based on chalcogen-thiophene (n-Bu4S) and selenophene (n-Bu4Se) having tetra-pyridine as bridge are developed to passivate defects in perovskite film. The uncoordinated Pb2+ and iodine vacancy defects can interact with chalcogen-concave group and pyridine group through the formation of the Lewis acid-base adduct, particularly both the defects can be surrounded by concave molecules, resulting in effective suppression charge recombination. This approach enables a power conversion efficiency (PCE) as high as 25.37% (25.18% certified) for n-i-p PSCs with stable operation at 65 °C and 1-sun illumination for 1300 hours in N2 (ISOS-L-2 protocol), retaining 94% of the initial efficiency. Our work provides insight into the bowl-shaped Lewis base in defects passivation by coordinated strategy for high-performance photovoltaic devices.